Maximizing the Implementation of Scientific Approach in History Lessons Through Student-Centered Learning Model - Ratnasari, Novika; Kurniawati, Kurniawati; Syukur, Abdul (Journal of Education Research and Evaluation, 2020)
Curriculum changes and developments occur along with the development of educational theory and technological developments. These changes aim to improve the quality of education of Indonesia's human resources. The 2013 curriculum emphasizes the learning process using a scientific approach. The purpose of this study was to analyze the scientific approach in the 2013 curriculum in the implementation of history learning. The type of research used was a qualitative approach. This research was conducted at SMA Negeri 1 Babat Toman Musi Banyuasin. In this study, data were collected usingÂ  observation, interviews, and document study method. Descriptive data analysis was used in this study. The results of this study indicate that the implementation of history learning in 2013 curriculum that uses a scientific approach through the Student-Centered Learning model and authentic assessment with 5 M (observing, asking questions, collecting data, associating, communicating) maximize learning by following the 2013 curriculum development. This study as a reference material to maximize other subject in accordance with 2013 curriculum development.